High-Quality Genome Assembly of Eriocheir japonica sinensis Reveals Its Unique Genome Evolution - Tang, Boping; Wang, Zhongkai; Liu, Qiuning; Zhang, Huabin; Jiang, Senhao; Li, Xinzheng; Wang, Zhengfei; Sun, Yue; Sha, Zhongli; Jiang, Hui; Wu, Xugan; Ren, Yandong; et al. (Frontiers in Genetics, 2020)
As an important freshwater aquaculture species in China, the Chinese mitten crab (Eriocheir japonica sinensis) has high economic and nutritional value. However, limited genomic information is currently available for studying of basic development and genetic diversity. Here, we performed whole-genome sequencing, assembly, and annotation based on third-generation genome sequencing technology. The size of the E. j. sinensis assembled genome was approximately 1.27 Gb, close to the estimated size (1.19 Gb), with a contig N50 length of 3.19 Mb. Furthermore, based on assessment using Benchmarking Universal Single-Copy Orthologs (BUSCO), 94.00% of the expected eukaryotic genes were completely present in the genome assembly. In addition, repetitive sequences accounted for ~61.42% of the assembled genome, and 22,619 protein-coding genes were annotated. Comparative genomics analysis demonstrated that the Chinese mitten crab diverged from Penaeus vannamei ~373.6 million years ago, with a faster evolution rate than shrimp. We anticipate that the annotated high-quality genome of E. j. sinensis will promote research on its basic development and evolution and make substantial contributions to comparative genomic analyses of crustaceans.